’Uitgebreid naar gelang het onderwijs zulks vereischt’ Het instrumentenkabinet van de Rijks Hogere Burgerschool te Groningen - Zuidervaart, Huib (Studium, 2018)
In this article some personal recollections are presented about scientific instruments inspected in 1977 in the repository – and on the attic – of the former Rijks Hogere Burgerschool, built in Groningen in 1868-1869.